2022
DOI: 10.1177/08445621221097520
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Canadian Medical Delays and Preventive Measures on Breast Cancer Experience: A Silent Battle Masked by the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic led to the prioritization of breast cancer services towards patients who are currently in treatment or diagnosed with advanced stages of breast cancer, and the self-assessment of both tumor growth and treatment side effects. Alongside the stress associated with cancer itself, delays and complications due to COVID-19 may impact patients’ mental health. Purpose To describe the experiences of Canadians living with breast cancer who received a diagnosis and/or treatment during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…The same finding was true for approximately 75% of prediagnosis and recently diagnosed patients [35]. In another Canadian study, patients reported feeling dehumanized while receiving their medical care for breast cancer [33]. Taken together, a higher proportion of patients presenting with metastatic disease in our analysis would be consistent with this interruption in care, the pandemic having coincided with our retrospective timeframe (2021 to 2023).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The same finding was true for approximately 75% of prediagnosis and recently diagnosed patients [35]. In another Canadian study, patients reported feeling dehumanized while receiving their medical care for breast cancer [33]. Taken together, a higher proportion of patients presenting with metastatic disease in our analysis would be consistent with this interruption in care, the pandemic having coincided with our retrospective timeframe (2021 to 2023).…”
Section: Discussionsupporting
confidence: 78%
“…(2) the entry criteria of the study were skewed for higher-risk, more progressive patients; and (3) the COVID-19 pandemic influenced timely access to care. The impact of the COVID-19 pandemic on the spectrum of cancer care, including delaying diagnoses and treatment, is well documented [30][31][32][33]. For example, provincial breast cancer screening programs were suspended for several months during the pandemic [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds to the growing body of work that has demonstrated how COVID-19-related treatment delays among breast cancer patients lead to increased anxiety and depression [18][19][24][25][26][27]. For example, one Korean study of 154 breast cancer patients found that COVID-19-related treatment changes signi cantly correlated with depression [19].…”
Section: Discussionmentioning
confidence: 71%
“…This observation sheds light on the potential impact of COVID-19 on both patient- and facility-related management delays. Furthermore, these two factors could help explain the differences in patient presentations before and after the COVID-19 pandemic, as reported in the literature [ 20 , 21 ]. However, it is worth noting that other variables, such as age and comorbidity, did not show a statistically significant association in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hawrot's study documented a median duration of 23 days from presentation to histological diagnosis [ 20 ]. Additionally, Fortin's study demonstrated that the timing of BC diagnosis and treatment nearly doubled during the pandemic compared to pre-pandemic times [ 21 ].…”
Section: Discussionmentioning
confidence: 99%